Gender difference in mathematics achievement among the graduates of BRAC schools - Nath, Samir Ranjan (BRAC Research and Evaluation Division (RED), 2020)
This study aims to explore the gender difference in mathematics achievement of the graduates of BRAC schools. Data generated in the numeracy section of the study on assessment of basic competencies of the graduates of BRAC schools of 1997 were analysed for this purpose. Two types of BRAC schools, viz., NFPE and BEOC, were considered in this study. Both bi-variate and multivariate approach were used to analyse the data. The findings of this study clearly showed that achievement in mathematics is significantly lower among girls than boys in BRAC schoQls (p<O.OOl). The gender variation was observed in both types of schools, however, the graduates of BEOC are more likely to do better in the test than the graduates of NFPE. Some suggestions were also made to improve the situation towards gender equity in mathematics learning in BRAC schools.